LOFAR early-time search for coherent radio emission from GRB 180706A. Issue 3 (21st October 2019) - Rowlinson, A; Gourdji, K; van der Meulen, K; Meyers, Z S; Shimwell, T W; ter Veen, S; Wijers, R A M J; Kuiack, M J; Shulevski, A; Broderick, J W; van der Horst, A J; Tasse, C; et al.
ABSTRACT: The nature of the central engines of gamma-ray bursts (GRBs) and the composition of their relativistic jets are still under debate. If the jets are Poynting flux dominated rather than baryon dominated, a coherent radio flare from magnetic reconnection events might be expected with the prompt gamma-ray emission. There are two competing models for the central engines of GRBs; a black hole or a newly formed millisecond magnetar. If the central engine is a magnetar it is predicted to produce coherent radio emission as persistent or flaring activity. In this paper, we present the deepest limits to date for this emission following LOFAR rapid response observations of GRB 180706A. No emission is detected to a 3σ limit of 1.7 mJy beam −1 at 144 MHz in a 2-h LOFAR observation starting 4.5 min after the gamma-ray trigger. A forced source extraction at the position of GRB 180706A provides a marginally positive (1σ) peak flux density of 1.1 ± 0.9 mJy. The data were time sliced into different sets of snapshot durations to search for FRB like emission. No short duration emission was detected at the location of the GRB. We compare these results to theoretical models and discuss the implications of a non-detection.